Financial Performance Analysis with a Common Size Approach at PT Kusumasejati Intiprima Bogor - Yuppy Triwidatin; M. Awalul Fahmi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This study aims to determine the financial performance of PT Kusumajati Intiprima Bogor with a common sizes analysis approaches. The design of this research is descriptive quantitative research , namely research with data in the form of numbers which are then processed and analyzed to draw conclusions . The data source used is secondary data in the form of balance sheets and income statements for 2015-2020. The results of this study indicates that the financial performance achieved by PT Kusumajati Intiprima Bogor from 2015 to 2020, the composition of the financial statements of PT Kusumajati Intiprima Bogor can said to low risk (safe) and the percentages of each assets and liability items fluctuate and PT Kusuma Sejati Intiprima Bogor has not been able to control operating costs which causes a decrease in net profit every year and becomes a loss.